Stress fracture of the femoral neck: a typical cause of hip pain - Khirul Ashar, Nur Ayuni; Hussin, Paisal; Mawardi, Maliza; Yeak, Raymond Dieu Kiat; Ponnidurai, Philemon Paul (Türkiye Acil Tıp Derneği, 2019)
As femoral neck stress fracture is a rare condition, it is often initially missed diagnose. This case report describes it in a lady with sedentary lifestyle following sudden strenuous exercise which presented with acute hip pain. Without high index of suspicion, fracture can be displaced further and its sequelae such as non-union, malunion and avascular necrosis are often disabling.Stress fracture is a rare condition. It is more common in the tibia, navicular, metatarsal and fibula while femoral neck only occupies 5% from the total cases. Hence, it is uncommon and may pose as a diagnostic challenge. It occurs in individuals that exert force or repetitively apply force to the healthy bone, commonly in athletes and military recruits with repetitive high intensity exercises and training. Due to this load, the bone undergoes a surge amount of bone resorption, however with strenuous activity and lack of rest in between, bone formation is unable to compensate the loss thus leading to microfracture. A break in the cortex may occur with the continuous stress.